Evaluation of Antibacterial Properties of Essential Oil of Malva Sylvestris Collected from Meshkinshahr on Common Bacteria of Oral Infection and Comparison with Chlorhexidine Mouthwash - Hojjat Eghbal; Arezou Mohammadi; Nima Mohammad Nejad Khiavi; Neda Jahani (Fasa University of Medical Sciences, 2020)
Background & Objective: Malva sylvestris, one of the most important plants used in the pharmaceutical, cosmetic and health industries in most developing countries, has antiseptic properties. Therefore, this research aimed to study essential oil components of Malva sylvestris juice collected from Meshkinshahr and its anti-bacterial property compared to chlorhexidine mouthwash on common bacteria of oral infection. Materials & Methods: In this research, Malva sylvestris was collected from the Anzan Meshkin-Shahr area in the northwest of Iran. The essential oil was extracted by Clevenger's apparatus, GC and GC/MS devices were used for the analysis of essential oil compounds and accurate measurements of the compounds. Then, the effect of the essential oil of the Malva sylvestris and control on the common bacteria of the oral infection was evaluated in two ways: Disc diffusion And minimum inhibitory concentration(MIC). Results: According to the results, the essential oil of the herb has a significant inhibitory effect on the types of gram-negative and positive bacteria. Also, comparing the diameter of the non-growth of the plant with chlorhexidine , it was found that the essence of the herb medicine showed relatively similar results to that of the chlorhexidine. Conclusion: According to the findings, the essential oil of the herb has a good anti-microbial effect against the common bacteria of oral infections. As a result, the essential oil of this plant with different concentrations, after completing studies, can be an appropriate alternative for chemical drugs and chemical mouthwashes in the treatment of oral bacterial infections.